From inscriptions to grammar: notes on the grammar of non-Sabaic languages - Avanzini, Prof. Alessandra (Proceedings of the Seminar for Arabian Studies, 2014)
The corpus of Sabaic inscriptions is ample and covers a broad geographical area, as well as a vast span of time. The German school of Ancient South Arabian studies, created by Professor Müller, has greatly added to our knowledge of the Sabaic language; many grammatical traits have been defined and some of their geographical and chronological variations identified. Texts written in minuscule allow us to study a different cultural and social level of the Sabaic language, not conveyed by monumental inscriptions. A smaller number of inscriptions in the Minaic, Qatabanic, and Hadramitic languages have come down to us. In this paper various linguistic traits and rules governing the written form of these non-Sabaic languages will be presented, including the use of the maires lectionis in writing vowels, and the declension of nouns. As is always the case with dead languages, the grammatical rules that can be singled out are those transmitted by a specific writing school. Nevertheless, some of the linguistic variations that were introduced into the non-Sabaic languages over time and across geographic areas can be identified.